Providing English and native language quotes in qualitative research: A call to action - Ahtisham Younas; Sergi Fàbregues; Angela Durante; Parveen Ali (Wiley, 2022)
Abstract Background When publishing qualitative research in international journals, researchers studying non‐English‐speaking participants provide quotes in English language. This is an issue of increasing concern given the need to be rigorous to represent a diversity of participants within their context, beyond how language (alone) situates them. Aim To argue for providing English and native language quotes in qualitative research reports. Design Discussion. Methods This paper is based on the literature on use of quotes and translation in qualitative research and authors' experiences of publishing qualitative research. Results Provision of native and English language quotes may allow for greater transparency of findings, thereby reflecting that the researchers adequately captured the socially and culturally dependent experiences of participants. Conclusions Presentation of findings with eloquent quotes serves as the gateway into the sociocultural experiences of individuals. We argued against the norm of providing translated quotes in qualitative reports and build a case for the provision of native as well as English language quotes to promote cross‐cultural understanding.